Which Patients with Giant Cell Arteritis Will Develop Cardiovascular or Cerebrovascular Disease? A Clinical Practice Research Datalink Study - Robson, J; Kiran, A; Maskell, J; Hutchings, A; Arden, N; Dasgupta, B; Hamilton, W; Emin, A; Culliford, D; Luqmani, R (Journal of Rheumatology, 2016)
Objective. To evaluate the risk of cerebrovascular disease and cardiovascular disease (CVD) in patients with giant cell arteritis (GCA), and to identify predictors. Methods. The UK Clinical Practice Research Datalink 1991–2010 was used for a parallel cohort study of 5827 patients with GCA and 37,090 age-, sex-, and location-matched controls. A multivariable competing risk model (non-cerebrovascular/CV-related death as the competing risk) determined the relative risk [subhazard ratio (SHR)] between patients with GCA compared with background controls for cerebrovascular disease, CVD, or either. Each cohort (GCA and controls) was then analyzed individually using the same multivariable model, with age and sex now present, to identify predictors of CVD or cerebrovascular disease. Results. Patients with GCA, compared with controls, had an increased risk SHR (95% CI) of cerebrovascular disease (1.45, 1.31–1.60), CVD (1.49, 1.37–1.62), or either (1.47, 1.37–1.57). In the GCA cohort, predictors of “cerebrovascular disease or CVD” included increasing age, > 80 years versus < 65 years (1.98, 1.62–2.42), male sex (1.20, 1.05–1.38), and socioeconomic status, most deprived quintile versus least deprived (1.34, 1.01–1.78). These predictors were also present within the non-GCA cohort. Conclusion. Patients with GCA are more likely to develop cerebrovascular disease or CVD than age-, sex-, and location-matched controls. In common with the non-GCA cohort, patients who are older, male, and from the most deprived compared with least deprived areas have a higher risk of cerebrovascular disease or CVD. Further work is needed to understand how this risk may be mediated by specific behavioral, social, and economic factors.